We are the stars : colonizing and decolonizing the Oceti Sakowin literary tradition - Hernandez, Sarah (Sarah Raquel) (Critical issues in indigenous studies., 2023)
"We are the Stars critically interrogates the U.S. as a settler colonial nation and re-centers Oceti Sakowin women as our tribe's traditional culture keepers and culture bearers"--